Quranic Archaeology as a Knowledge Branch of Archaeology - Ali Akbar (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2012)
Archaeology has not paid adequate attention on Qur'anic studies yet; meanwhile, a lot of Biblical Archaeology researches are already available. This paper tries to formulate the branch of archeology, called Quranic Archaeology. As a branch of knowledge, this Quranic Archaeology must fulfill the archaeological scientific standard for the purpose of developing Quranic Archaeology as presented in this paper. This scientific basis is then depicted in various research topics for its development underpinned by research examples to trigger the development of knowledge and social dynamics.